Valoración geriátrica integral y mapa de distribución geográfica en adultos mayores de la ciudad de Iquitos, 2024 - Paredes Obando, Marco Fabrizio (2024)
Objectives: To develop the Comprehensive Geriatric Assessment and the Geographic Distribution Map of Older Adults in four districts (Iquitos, Belen, San Juan Bautista and Punchana) of the city of Iquitos, Loreto, Peru in the year 2024. Methods: Observational, cross-sectional study that surveyed 180 older adults, 45 for each district with distribution by clusters (4 clusters per district). Results: Of the 180 older adults, the population was predominantly female (58.9%), aged 65-74 years (54.4%), with primary education (55.8%) and low income (62.2%). High rates of frailty (71.7%), risk of falls (51.1%), functional dependence in basic activities of daily living (55.6%), functional dependence in instrumental activities of daily living (71%) and risk of malnutrition (55.4%) were observed. Mental assessment showed significant prevalence of mild depressive symptoms (33.9%) and 36.7% some degree of cognitive impairment, while social assessment indicated generalized impairment. Significant differences were found between the four districts studied in sociodemographic factors and geriatric assessments, with distinctive geographical patterns in aspects such as socioeconomic level, rational polypharmacy, overweight and functional dependence (p<0.05). Conclusions: The high proportion of older adults with multiple health and functional problems, together with the geographical variations identified, highlight the urgent need to implement comprehensive geriatric health programs adapted to the regional context.